Adapting the Parent Connector program for caregivers of adults with SMI: the Family Connector experience - Paige E. Cervantes; Charlotte Gendler; Lori Markowitz; Meggin Rose; Priscilla Shorter; Sally Mason; Tanya Hernandez; Kimberly E. Hoagwood (npj Mental Health Research)
Abstract Caregivers play an essential role in the recovery of their adult loved ones with serious mental illness (SMI). Promoting caregiver empowerment and well-being is critical but has often been overlooked. Family peer interventions are well-suited to fill this need; however, research is limited supporting their use with caregivers of adults with SMI. Our team is currently engaged in a study evaluating an adapted version of the evidenced-based Parent Connectors program1,2, renamed Family Connectors (FC), for caregivers of young adults recently discharged from the First Episode Psychosis program in New York (OnTrackNY). This paper, written collaboratively with family peer professionals, describes the adaptation process we followed to systematically document the family peer professional experience one year into delivering the FC program to this novel population. Modifications made to improve intervention fit included tailoring the content of the intervention, incorporating an outside approach into the program, lengthening the service in some cases, and adding a weekly peer supervision meeting. We hope that these insights are used to inform future efforts to advance support for families of loved ones with SMI, and more broadly, that our approach serves as a model for effective collaboration to improve the application of peer support services for unique groups.